Effectiveness of a nurse-led coaching in self-care intervention for elderly undergoing total laryngectomy: a randomised controlled trial - Yan Liu; Lai Wei; Xue Li; Jian Chen; Huifen Wang; Liyuan Zheng; Shu'e Liu; Danxia Peng; Sanxia Ye; Yuchen Lu; Zhidan Mei; Chun Xu (BMJ Open)
Objectives To evaluate the effectiveness of nurse-led coaching in self-care (SC) interventions for elderly patients undergoing total laryngectomy (TL) using multidimensional parameters.Design This was a double-arm randomised, single-centre trial that met the requirements of the CONSORT statement.Setting Head and neck department in a tertiary A-level hospital.Intervention Elderly patients scheduled for TL were randomly allocated to either the control group (n=24) or the intervention group (n=23). Patients in the control group received routine nursing care during hospitalisation and, subsequently, at home after discharge, received conventional family care without the regular supervision of nurses. Patients in the intervention group received a series of SC interventions led by nurses during hospitalisation and discharge and implemented SC practice using the home SC manual (SC knowledge and SC diary), nurses regularly supervised and evaluated the SC effect. The primary outcome was the SC ability. Secondary outcomes were self- efficacy, quality of life (QoL) and nutritional status.Results The SC intervention improved the SC ability, self-efficacy, QoL and nutritional status scores of patients in the intervention group compared with that of patients in the control group (p<0.01). The outcomes showed that the intervention had a significant effect on SC ability, self-efficacy and QoL scores, with both the main effects of time and intervention, as well as their interaction being significant (p<0.05). Nutritional status, as assessed using the PG-SGA, was better in the intervention group than in the control group (p<0.001). No adverse events (AEs) were observed in either group.Conclusion Nurse-led SC intervention for elderly patients with TL is an effective strategy that can bring multidimensional benefits, including higher self-efficacy, stronger SC ability to actively solve health problems, better QoL and nutritional status, as well as shorter hospital stays.Trial registration number ChiCTR2100043731.